ESTIMASI PERMINTAAN ENERGI LISTRIK PENDUDUK PROVINSI RIAU (Studi Kasus Pelanggan Rumah Tangga PLN Riau) - , Indra Gunawan, ST; , Dr. Faried Wijaya Mansoer, M.A., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Estimating household electricity demand in different regions is very important to be done, especially in areas with characteristics such as Indonesia, because the estimated electricity demand per region will provide a clearer picture than the estimated power demand of a country as a whole. Estimated demand for electricity is an anticipatory measure to avoid electricity crisis, which also serves as a benchmark for economic planning and development. This research was aimed at understanding the determinants of electricity demand in the province of Riau. Econometrics is an appropriate method to estimate electricity demand. This research used time series data during the period 2002-2010 including the total electricity consumption by PLN household customers in Riau, Riau population, GDP per capita in Riau and electricity price average in Indonesian for household consumers. Four estimation models were used, two of which were categorized as static model with OLS technique, and the other two were dynamic models with ECM approach. Stationary data and co-integration test were chosen as preliminary estimation procedures, which relied on ADF method and Johansen co-integration technique. The OLS estimation results indicate that the number of population and income were determinants of electricity demand in the province of Riau, while electricity price did not shown any significant effect. The estimation results using ECM models can be ignored because they are not statistically significant. Multicollinearity problems which can possibly occur in regression model can be ignored because each variable has a VIF value of less than five.